Kerangka kesedaran kognitif bagi reka bentuk antaramuka pengajaran berasaskan gamifikasi dalam kalangan pelajar kejuruteraan - Zakaria, Zakiah (2020)
Gamification is one of the most popular methods of teaching today. The usage of gamification appropriately applied to students will contribute to their learning. In the global world of education, the use of gamification affects the quality of their learning. This study discuses the elements of gamification design that contribute to the awareness of cognitive learners. A total of 400 UTHM students comprising of engineering students answer the questionnaire was developed to determine the criteria involved in cognitive awareness in developing gamification learning. The findings of the survey were analyzed using statistical descriptive. In addition, data found in survey questions are used for literature review to analyse the criteria for gamification to enhance cognitive awareness through content analysis and the targeted literatures are journals, conferences and books available in the database from 2015 to 2018. Both survey and literature review analys were used to indentify cognitive domain awareness criteria in gamification in learning design. In order to verify and validate the criteria, a checklist was used involving three experts in the field of gamification. This data is analyzed through heuristic analysis. Next, the data was verified and validated by the expert. The data was analysed using an interpretation of cohen kappa result. The overall findings determined the criteria of cognitive awareness in gamification learning for engineering students. It is hoped that the criteria for cognitive awareness will help to improve the decision-making process and the ability to evaluate students performance.